THE EFFECT OF THE SOMATOSTATIN ANALOGUE OCTREOTIDE ON EXPERIMENTAL INTESTINAL OBSTRUCTION IN RATS - Paran,Haim (1998)
Background: Somatostatin has an inhibitory effect on the endocrine and exocrine secretions of the gut. It may have a beneficial effect in the conservative treatment of intestinal obstruction. The aim of the present study is to investigate the effect of octreotide in mechanical intestinal obstruction in rats. Method: Intestinal obstruction was induced in rats by ligation of a segment of the distal ileum. Animals were treated with the somatostatin analogue octreotide (n=16), or saline (n=16). Eight rats were operated but their intestine was not ligated (n=8) serving as sham controls. Forty eight hours after the operation, the animals were operated upon again and blood samples from the femoral vein were tested for electrolytes, urea, glucose, lactic acid, amylase, ph and bicarbonate. Portal vein blood samples were also obtained and tested for lactic acid and amylase. Results: Intestinal obstruction resulted, after 48 hours, in severe dilatation of bowel loops. A significant increase in plasma levels of urea, amylase and lactic acid was observed. Plasma pH decreased. In blood samples from the portal vein, a significant increase in lactic acid was observed, indicating metabolic acidosis, probably secondary to bowel ischemia. Octreotide treatment, resulted in less acidosis, with concomitant lower urea and lactic acid levels in the plasma and especially in the portal vein. Conclusion: Octreotide treatment may have a beneficial effect in the conservative treatment of selected cases of intestinal obstruction.